Economics and politics of the bolivian model 2006-2014: preliminary assessment - Arevalo Luna, Guillermo Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Bolivia suffered a profound political and socioeconomic change withinthe period 2006– 2014, shifted from a liberal development model to amixed economy. The State has a complete control of economic resourcesand main incomes of industry. The surplus generated by commoditiescontributed to the income distribution policy and also was used for fightingagainst poverty by a better education and health. The macroeconomicmodel was successful: the Bolivian economy grew at an average rate of4.6% yearly during the period 2006–2014 and registered a fiscal surplus,a positive trade balance and an increase in the volume of international reserves.Now the country has macroeconomic stability and low inflation.